DLAT is involved in ovarian cancer progression by modulating lipid metabolism through the JAK2/STAT5A/SREBP1 signaling pathway - Hui Wang; Shen Luo; Yue Yin; Yang Liu; Xiaomei Sun; Ling Qiu; Xin Wu (Cancer Cell International)
Abstract Background Ovarian cancer (OC) remains a lethal gynecological malignancy with an alarming mortality rate, primarily attributed to delayed diagnosis and a lack of effective treatment modalities. Accumulated evidence highlights the pivotal role of reprogrammed lipid metabolism in fueling OC progression, however, the intricate underlying molecular mechanisms are not fully elucidated. Methods DLAT expression was assessed in OC tissues and cell lines by immunohistochemistry, western blot and qRT-PCR analysis. The effects of DLAT silencing on changes in lipid metabolism, cell viability, migration, and invasion were examined in SKOV3 and OVCAR3 cells using CCK-8, colony formation, Transwell migration and invasion, and wound-healing assays. GSEA analysis was used to examine the relationship between DLAT and lipid metabolism-related enzymes. Rescue experiments in which SREBP1 was overexpressed in DLAT-silenced cells were carried out. Western blot analysis was performed to determine whether the JAK2/STAT5 signaling pathway was involved in DLAT-regulated SREBP1 expression. Commercially available triglyceride and cholesterol detection kits, as well as Nile Red and Oil red O staining were used to measure lipid metabolism. A subcutaneous tumor model was established in BALB/c mice to confirm the role of the DLAT/SREBP1 axis in OC growth and metastasis in vivo. Results DLAT expression was significantly upregulated in OC patient tissue and associated with poor prognosis. Silencing DLAT reduced lipid content and impaired OC cell proliferation, migration, and invasion. DLAT upregulated SREBP1 expression via the JAK2/STAT5 signaling pathway, enhancing expression of fatty acid synthesis enzymes and altering lipid metabolism. SREBP1 was essential for DLAT-dependent OC cell growth and metastasis both in vitro and in vivo. Conclusion This study uncovers a novel DLAT/JAK2/STAT5/SREBP1 axis that reprograms lipid metabolism in OC, providing insights into metabolic vulnerabilities and potential therapeutic targets for OC treatment.